Original paperAugmented immunoexpression of survivin correlates with parameters of aggressiveness in prostate cancer - Danilewicz, Marian; Stasikowska-Kanicka, Olga; Wągrowska-Danilewicz, Małgorzata (Polish Journal of Pathology, 2015)
The clinical significance of the immunoexpression of survivin in prostate cancer and its correlation with the biological aggressiveness of prostate cancer remains unclear. Therefore, the present study was undertaken to compare the immunoexpression of survivin in prostate cancer (PCa) and benign prostatic hyperplasia (BPH) as well as to determine whether this immunoexpression could correlate with Gleason score, proliferation activity and prostate specific antigen (PSA) levels. The prostate needle biopsies from 28 patients with elevated serum PSA levels were studied. As a control, 12 needle biopsies of prostate diagnosed as BPH were used. The immunoexpression of survivin was evaluated semiquantitatively, whereas the Ki-67 index was assessed quantitatively. The immunoexpression of survivin and Ki-67 in epithelial cells in the prostate cancer group was significantly increased as compared to BPH cases. In the prostate cancer group there were positive significant correlations between the immunoexpression of survivin and Gleason score as well as Ki‑67 antigen. The correlation between the immunoexpression of survivin and PSA levels was also positive, but it did not reach statistical significance. In conclusion, we can confirm that in prostate cancer the immunoexpression of survivin is augmented as compared to BPH and positively correlated with parameters of tumor aggressiveness.